Neuropsychological considerations for long-duration deep spaceflight - Faerman, Afik; Clark, Jonathan B.; Sutton, Jeffrey P. (Frontiers in Physiology, 2023)
The deep space environment far beyond low-Earth orbit (LEO) introduces multiple and simultaneous risks for the functioning and health of the central nervous system (CNS), which may impair astronauts’ performance and wellbeing. As future deep space missions to Mars, moons, or asteroids will also exceed current LEO stay durations and are estimated to require up to 3 years, we review recent evidence with contemporary and historic spaceflight case studies addressing implications for long-duration missions. To highlight the need for specific further investigations, we provide neuropsychological considerations integrating cognitive and motor functions, neuroimaging, neurological biomarkers, behavior changes, and mood and affect to construct a multifactorial profile to explain performance variability, subjective experience, and potential risks. We discuss the importance of adopting a neuropsychological approach to long-duration deep spaceflight (LDDS) missions and draw specific recommendations for future research in space neuropsychology.